The Tourism Impact on the Residents’ Life Quality – Case Study - Pedro LIBERATO; Ana SILVA (Communications of International Proceedings, 2020)
Tourism is a fast-growing sector at national level, but also at global level. This growth has generated positive externalities, but also some negative ones. This study aims to understand how the (negative) impacts of tourism are perceived by residents of the Sé parish, and how they affect their quality of life. To achieve the main objective of the study, a face-to-face survey was carried out among the inhabitants of the parish of the Sé. The answers of 234 participants were collected and then analysed in the SPSS statistical software. The results obtained prove that the residents have quality of life, are satisfied with the conditions of their environment, noting also that these two variables are related to each other. However, it was not possible to correlate residents' perceptions regarding the role of tourism activity. Through the results obtained it is expected that tourist entities and bodies evaluate, the growth and maintenance of tourism, but also all the issues that are directly or indirectly related to it.
Keywords: Gentrification; Tourist Pressure; Overtourism; Quality of Life.